Surface elastic properties in silicon nanoparticles. (6th December 2017) - Melis, Claudio; Giordano, Stefano; Colombo, Luciano
Abstract: The elastic behavior of the external surface of a solid body plays a key role in nanomechanical phenomena. While bulk elasticity enjoys the benefits of a robust theoretical understanding, many surface elasticity features remain unexplored: some of them are here addressed by blending together continuum elasticity and atomistic simulations. A suitable readdressing of the surface elasticity theory allows to write the balance equations in arbitrary curvilinear coordinates and to investigate the dependence of the surface elastic parameters on the mean and Gaussian curvatures of the surface. In particular, we predict the radial strain induced by surface effects in spherical and cylindrical silicon nanoparticles and provide evidence that the surface parameters are nearly independent of curvatures and, therefore, of the surface conformation.